Integrated Postsecondary Education Data System (IPEDS): Fall Enrollment, 1992 ([Verlag nicht ermittelbar], 1999)
The Fall Enrollment survey is conducted annually by the National Center for Education Statistics (NCES) as part of the Integrated Postsecondary Education Data System (IPEDS). The survey is sent to accredited institutions of higher education and to all other institutions offering bachelor's, master's, doctoral, or first-professional degrees. In odd years beginning in 1987, the Fall Enrollment survey was expanded to collect student enrollment data by 11 age categories. In even years, the survey was expanded to collect residence data for first-time freshmen. There are three data files in this collection. Part 1, Institutional Characteristics, includes variables on control and level of institution, highest level of offering, accreditation status, Carnegie classification, and state FIPS codes and abbreviations. Part 2 covers enrollment data by race/ethnicity and level of student, while the focus of Part 3 is enrollment data for first-time, first-year students by state residence of student.